Improved Estimation of Air-to-Air Missile Aerodynamic Characteristics with Using CFD Method (Advances in Military Technology, 2020)
The paper describes a solving procedure of the special Finite Volume Method (FVM) problem dealing with calculation of a flow field around air-to-air missile at subsonic, transonic and supersonic velocity range in order to obtain a coefficient of drag (cD). Some emphasis is put on numerical solution and fundamentals of FVM and use of a k-ω turbulence model for simulation of subsonic and supersonic flow fieldsaround air-to-air missile AIM-9 Sidewinder version M. Obtained results of missile aerodynamics characteristics are verified using semi-empirical software and by analysis of flow fields.
Keywords: aerodynamic characteristics; CFD simulation; guided missile; k-ω turbulence model; trimmer mesh